The Effect of Vibration Maneuver on Pain Relief during Cannulation Insertion for Cancer Patients: A Randomized Controlled Trial - Kadhim, Alaa Jawad; Chenari , Hadi Ahmadi (Iraqi National Journal of Nursing Specialties, 2025)
Objective(s): To measure the effect of using vibration maneuver on the level of pain during intravenous cannulation.Methods: A randomized controlled trial was carried out in the oncology unit of AL- Al-Haboubi Teaching Hospital in Thi-Qar governorate from   November 22nd, 2023 to June 5th, 2024.  After the sample was selected among patients, 105 patients were divided into two groups, 50 in the control group and 55 in the experimental. In the experimental group, a vibrating device was used, and the pain was assessed using a visual analogue scale of a 10-cm line. The researcher used two white envelopes inside which there was a colored card to facilitate the random selection and a self-report method was used for data collection.Results: The results of the statistical analysis showed highly significant differences between the two groups in pain intensity during cannulation in the post-test. The control group recorded a high average pain intensity of (M+SD 76.54+20.427), While the experimental group showed a significant decrease in pain intensity with an average (M+SD 27.25+22.788). These results indicate that the intervention based on applying vibration technology contributed effectively to reducing the level of pain, as the difference between the two groups was highly statistically significant (p=0.001).Conclusion: The study concluded that vibration maneuver had a positive relationship and highly effective   in reducing pain for intravenous cannulation.Recommendations: The study recommended that the vibration experience be applied to patients during cannulation insertion in adult segments.